Application of FCE–AHP method for multi-criteria decision-making of municipal solid waste management alternatives: a case study in the Dalian Development Zone of China. (1st January 2011) - Du, Jing; Xu, Ling; Wang, Shuo; Yang, Fenglin; Adohinzin, Junior B.N.; Harashina, Sachihiko
Because of rapid economic and population growth as well as change in consumption patterns in last decades, municipal solid waste management (MSWM) has become an important strategic decision so that the evaluation and assessment process is attached a prime concern. Avoiding the injustice which may be caused by subjective factors, this paper sets up a hybrid model of fuzzy comprehensive evaluation and analytical hierarchy process for a MSWM alternative selection. A case study for MSWM alternative selection in Dalian Development Area of China is presented to demonstrate the practicality of this model. With an identification and design of a comprehensive and scientific evaluation index system, this paper furthermore proposes a detailed operation procedure of the selected option according to the simulation results.